Flebotomíneos insulares e infecção natural de Nyssomyia neivai por Leishmania, sul do Brasil - Santos, Barbara Andreo dos (2014)
Leishmaniasis are widely distributed and have great impact on public health worldwide. In Brazil, cutaneous leishmaniasis (CL) has been reported in all states and visceral leishmaniasisin twenty-one. This study aimed to determine the fauna and investigate the rate of natural infection by Leishmania in sandflies of islands of the Parana River, in the state of Parana.Sandflies were collected with Falcao traps in islands Mutum, Bandeira, Carioca and Fina,situated in the middle part of the Upper Parana River, northwest of the state of Parana. After identification, the female specimens of Nyssomyia neivai were subjected to Multiplex Polymerase Chain Reaction technique (Multiplex-PCR) for detection of Leishmania. Toperform this technique were employed two pairs of primers: i) MP3H and MP1L for amplification of fragment 70-bp region of the minicircle kinetoplast of Leishmania subgenus and ii) 5Llcac and 3Llcac, which amplify a fragment of 220-bp region the cacophony geneIVS6 in insects of the genus Lutzomyia, exercising internal control function of reaction. We recollected and identified specimens of Ny. neivai 19,818 of which 16,746 females and 3,072males, and two female specimens of Ny. Whitmani and one Psathyromyia Shannon female. Of the total of 378 (38 pools) females of Ny. neivai subjected to Multiplex-PCR was detected in an exemplary (0.26 %) infected by Leishmania (Viannia) sp. considering an insect infected foreach positive pool. Thus, we see once again the importance of this species in the epidemiology of CL, since this species has often been marked by natural infection by protozoa of the genus Leishmania. In addition, population density, geographic distribution, frequency outside the home and domicile, the anthropophily, the adaptation of this insect misanthropic environments and climatic conditions are factors that favor the persistence of enzootic cycle of Leishmania in endemic areas of CL. The detection Ny. neivai naturally infected by Leishmania in island Mutum highlights the need for research on the behavior of sand flies in the islands of the Parana River, especially those with permanent and temporary residents, and the need for intervention by public health services for the use of measures population control of these insects.